Assessment of the output of primary school fifth grade Koran - Mohammad Hasan Mirzā Mohammadi; Abdollāh Afshār; Rasul Shāhrezāyi; Mohtaram Ghobādi (فصلنامه نوآوری‌های آموزشی, 2013)
The aim of this research was evaluation of the output of primary school fifth grade Koran curriculum at the academic year of 1388-1389. The data included test scores on accuracy and speed of reading Koran and textbook of Koran education and also the viewpoints of students about their interest in the holy Koran. Data was collected using oral test of academic achievement and interest and attitude assessment questionnaire. The materials consisted of primary school fifth grade textbook of Koran education and the also the holy Koran. The data was analyzed using a variety of descriptive statistical methods (enumeration questions, percentage, frequency, mean, standard deviation, tables and graphs) and inferential statistics (one-way ANOVA, post hoc, and Chi-square test) depending on the type of data. In general, research has shown that primary school fifth grade students correctly read the Koran on average level. Although this result is acceptable, however it is not desirable. Given the nature of the education system, Koran education needs more careful planning. Also, the result showed that primary school fifth grade students could not read Koran with appropriate speed, as they read Koranic texts with rather low speed. Another finding of this study was that the accuracy of students’ ability in reading verses of the holy Koran was weaker than Koran education textbooks. So, it is necessary to use Koran more along with school textbooks. An interesting point is that although the accuracy and speed of Koran reading of primary school fifth grade students is not desirable, but they are interested in the Koran. Findings of attitude questionnaire showed that generally students’ attitudes have been positive. Therefore, Koran curriculum planners and practitioners should properly take advantage of this opportunity to take action to eliminate existing weaknesses. Another major finding of this study was that primary school fifth grade girls are better than boys in Koran reading. Overall, the outcome of primary school fifth grade Koran curriculum is acceptable, but not desirable. It is necessary for the planners and practitioners to act with sensitivity about this subject. Based on the research findings, some applied suggestions have been presented to improve students’ accuracy and speed in Koran reading.